Teaching Practice in Higher Educations (Docentes 2.0 Journal, 2026)
Teaching practice in higher education institutions is understood as part of the teaching-learning process that unfolds between teacher and student within a specific setting. The objective of this research was to analyze the characteristics, trends, and approaches of teaching practice in higher education, identifying the main contributions and limitations reported in previous studies. The research was conducted within the interpretive paradigm, using a systemic method, a qualitative approach, and a descriptive narrative design, of a documentary, bibliographic-analytical, and cross-sectional nature. This methodological structure allowed for the organization, description, and synthesis of relevant findings on the phenomenon under study. The research was based on the collection, selection, and critical synthesis of scientific sources published between 2019 and 2024, and was cross-sectional, analyzing information from a single time period. The results of the literature review reveal that teaching practice in higher education represents both a challenge and an opportunity, demanding a change that integrates pedagogical training, reflection, critical analysis, institutional commitment, and social responsibility.  Furthermore, it emphasizes the limited research on teaching practice in higher education, underscoring the need to address this gap in light of contextual demands. Therefore, reflection and methodological restructuring are urgently needed.
Keywords: Teaching practice; higher education; university education